Flipped Classroom Learning Effectiveness With Realistic Mathematics Approach To Student Learning Outcomes At MTS Azizi Medan T.P 2020/2021 - Elmuna Maulidina; Elfrianto Nasution (UMSU, 2021)
The formulation of the problem in this study is whether the flipped classroom learning model with a realistic mathematical approach is effective on the mathematics learning outcomes of students at MTs Azizi Medan T.P 2020/2021. The purpose of this study is to find out whether the flipped classroom learning model with a realistic mathematical approach is effective on the mathematics learning outcomes of students at MTs Azizi Medan T.P 2020/2021. The research design used in this study was a pretest posttest control group design. Sampling was done randomly. The instrument used in this study was a test (pretest and posttest in the form of a description). Based on the results of hypothesis testing using t-test at a significant level of 5% or 0.05 and degrees of freedom dk , obtained a value with a value of . Based on the increase test (N-Gain) that there is an increase in the experimental class by 0.5 and in the control class by 0.12. Therefore, it can be concluded that the flipped classroom learning model with a realistic mathematical approach is effective in improving student learning outcomes for class VIII MTs Azizi Medan T.P 2020/2021.